The effectiveness of different types of face masks - Queen G Wamungu; Joan Liverpool; Crystal Loney; Jodene Brevitte; Nirvani Goberdhan (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2020)
The Novel Coronavirus (COVID-19) continues to be a major health burden in many countries around the world with astonishing reports of fatalities. The burden on the health care systems around the world has been tremendous with a death toll of over 190,000 deaths in the US [1]. According to the World Health Organization (WHO), the Sars-CoV-2 virus that causes COVID-19 disease is spread via respiratory droplets [2]. According to a study published by Durgesh Sinha and Nicholas Klahn, from Tempa University and Rowan College at Burlington college respectively, on April 12th, 2020, titled "Mathematical modeling study of the 2020 Covid-19 outbreak in the United States", 40% - 80% of Covid-19 transmission arise from people who are pre-symptomatic or asymptomatic [3].